Influenza and Respiratory Syncytial Virus Infections in Pediatric Patients during the COVID-19 Pandemic: A Single-Center Experience - Aušra Steponavičienė; Sigita Burokienė; Inga Ivaškevičienė; Indrė Stacevičienė; Daiva Vaičiūnienė; Augustina Jankauskienė (Children, 2023)
The overlap of coronavirus disease 2019 (COVID-19) with other common respiratory pathogens may complicate the course of the disease and prognosis. The aim of the study was to evaluate the rates, characteristics, and outcomes of pediatric patients with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), respiratory syncytial virus (RSV), influenza A/B infections, and their coinfections. A single-center prospective cross-sectional study was performed at the pediatric emergency department in Vilnius from 1 October 2021 to 30 April 2022. In total, 5127 children were screened for SARS-CoV-2, RSV, and influenza A/B. SARS-CoV-2 PCR tests were positive for 21.0% of children (1074/5127). The coinfection rate of respiratory viruses (RSV, influenza A) in patients with COVID-19 was 7.2% (77/1074). Among the 4053 SARS-CoV-2 negative patients, RSV was diagnosed in 405 (10.0%) patients and influenza A/B in 827 (20.4%) patients. Patients with COVID-19 and coinfection did not have a more severe clinical course than those with RSV or influenza infection alone. RSV and SARS-CoV-2 primarily affected younger patients (up to 2 years), while the influenza was more common in older children (4–10 years). Patients infected with RSV were more severely ill, reflected by higher hospitalization proportion and need for respiratory support.